Implementation of Parental Strategies to Improve Child Vegetable Intake: Barriers and Facilitators - Millen, Lauren (Glob Pediatr Health, 2019)
Purpose. To qualitatively assess barriers and facilitators to implementing specific behavioral strategies to increase child vegetable intake during home dinner meals by low-income parents. Method. Parents (n = 49) of children (9-12 years) were asked to implement 1 behavioral strategy following each of 6 weekly cooking classes at community centers. Example strategies included serving vegetables first, serving 2 vegetables, and using a bigger spoon to serve vegetables. The following week, parents discussed how they used the strategy and barriers and facilitators to its use. Discussions were recorded, transcribed verbatim, and coded separately by strategy using NVivo Pro 11 software. Inductive, comparative thematic analyses were used to identify themes by strategy. Results. Most participants were multiethnic women aged 30 to 39 years with low food security. Time and scheduling conflicts limited involvement of children in vegetable preparation (Child Help strategy). The type of foods served and an unfamiliar serving style inhibited use of the MyPlate and Available/Visible strategies, respectively. Children’s dislike of vegetables limited use of the Serve Vegetables First and Serve 2 Vegetables strategies. Ease of use promoted use of the Bigger Spoon strategy. Conclusion. Educators could tailor application of specific parent strategies for low-income families based on child and environmental characteristics.